The role of peace in Kelsen and Lauterpacht's theories of international law - Krešić, Mario, pravnik (Array, 2019)
The purpose of this article is to analyze the role of peace in the theory of international law of Hans Kelsen and Hersh Lauterpacht. The 1960 shift in Kelsen' s approach to the role of peace will be elaborated in detail. Along with the theoretical account on the connection between peace and law, both authors have directed their theories to practical matters in the existing international legal system. At the end of the analysis, the similarities and differences between Kelsen and Lauterpacht will be described.